2014
DOI: 10.1155/2014/561506
|View full text |Cite
|
Sign up to set email alerts
|

Torsion of the Retroperitoneal Kidney: Uncommon or Underreported?

Abstract: Vascular torsion in a renal allograft after placement in the retroperitoneum is rare and has only been reported twice in the literature. It is an extrinsically mediated process that occurs at the vascular pedicle resulting in graft compromise and potential loss. Rapid diagnosis and immediate surgical intervention may salvage allograft function. Herein, we present a unique case of a 42-year-old male that developed renal allograft torsion following a second kidney transplant placed in the retroperitoneum. Immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…While torsion is much less common than other vascular complications, it should be included in the differential and diagnosed rapidly as immediate surgical intervention can salvage allograft function. Delays in diagnosis result in an increased risk of frank necrosis, acute cellular rejection, and possible transplant nephrectomy [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While torsion is much less common than other vascular complications, it should be included in the differential and diagnosed rapidly as immediate surgical intervention can salvage allograft function. Delays in diagnosis result in an increased risk of frank necrosis, acute cellular rejection, and possible transplant nephrectomy [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data is limited regarding salvage rates of extraperitoneal torsion given that only 3 cases have been reported in the literature. Of these cases, however, all resulted in salvage of the allograft without the need for nephrectomy [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Winter et al described a case of torsion they believe resulted from the patient's increased BMI and error in surgical technique [4]. In 2014, Sosin et al reported laxity of the abdominal wall and accompanying potential large retroperitoneal space as the primary factors leading to rotation of the graft [3]. We believe that our case represents yet another situation whereby an enlarged native polycystic kidney exerted pressure and caused rotation of the renal allograft about its pedicle.…”
Section: Discussionmentioning
confidence: 79%
“…Torsion of kidneys transplanted into the retroperitoneal space is a rare complication. Only three other cases have been reported, all within the last ten years [2][3][4]. These cases represent examples of warm ischemic time in kidney transplants.…”
Section: Introductionmentioning
confidence: 99%